Contributions to the knowledge of Antarctodon sobrali (Mammalia: Astrapotheria) from the Eocene of Antarctica - Gelfo, Javier Nicolás
The Astrapotheria constitutes one of the five orders of extinct South American native ungulates, with a fossil recordthat also extends to the Eocene of the Antarctic Peninsula. In contrast to the abundant specimens known for litopternSparnotheriodontidae and metatherians, astrapotheres are represented by scant remains assigned to the endemic Antarctodonsobrali and indeterminate astrapotheres, restricted to levels 35Cu0 and 35n of the Cucullaea I Allomember of the La MesetaFormation. The discovery of a lower molar assignable to this species in the Eocene levels of Seymour (Marambio) Island,enables a revision of the diagnosis and the homologies of the dental characters used to describe this taxon. A reanalysis of itsphylogenetic relationships reveals the nearly simultaneous presence of basal astrapotheres in the early Eocene of Itaboraí(Brazil), Patagonia, and West Antarctica. These taxa are characterized by lacking dental specializations usually associated withmore abrasive diets like terminal forms of Uruguaytheriinae and Astrapotheriinae. Antarctodon appears to have thrived on theAntarctic continent during the Early Eocene Climatic Optimum within the paleoclimatic context of a hot-house world. Unlikepresent conditions in Antarctica where no terrestrial mammals inhabit, the early Eocene climate was characterized by warmertemperatures and a biologically diverse environment rich in primary producers, dominated by Nothofagus forests, encompassingboth deciduous and evergreen forests, which supported a diverse assemblage of continental vertebrates. Fil: Gelfo, Javier Nicolás. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina